Study of on-demand COPE-aware routing protocol in wireless mesh networks - FAN Kai; LI Ling-xiong; LONG Dong-yang (Tongxin xuebao)
A new wireless routing protocol called OCR was presented, enhancing throughput of unicast traffic in wireless mesh networks （WMN）. In the routing discovery, OCR could actively detect the possible coding opportunities and make a tradeoff among these factors: utilizing the coding opportunities, finding the shortest path and neatly avoiding the congestion. The simulation results show that the network throughput can be greatly improved by OCR, compared to the traditional routing protocol, when using COPE.